Effects of Dietary Selenium on Paraoxonase and Arylesterase Enzyme Activities in Freshwater Crayfish Astacus leptodactylus - Yonar, Serpıl Mıse; Harlıoğlu, Muzaffer Mustafa (My University, 2019)
In this study, the effects of selenium added to the diets of Astacus leptodactylus at different ratioson paraoxonase (PON) and arylesterase enzyme activities (ARE) in the hepatopancreas and gonadtissues were investigated. In this study, control (K), trial 1 (D1), trial 2 (D2) and trial 3 (D3) wereprepared at the selenium levels of 0,3, 0,6, 0,9 and 1,2 mg/kg, respectively. The crude protein andtotal energy levels of experimental diets were equalized. 12 ponds in 2 × 2 × 1 m dimensions wereused. 75 female and 25 male crayfish were stocked in each pond (totally 1200 crayfish). This studywas carried out in triplicate. The crayfish were fed twice a day during 9 months. PON and AREenzyme activities were investigated in the tissue samples taken monthly from the crayfish. Duringthe trial, significant differences were observed in the PON and ARE enzyme activities in thehepatopancreas and gonad tissues. The PON and ARE enzyme activities increased statisticallysignificant in the crayfish tissues during the breeding season and incubation period. This increasewas found to be statistically different in the D1, D2 and D3 groups compared to the control group.In conclusion, selenium had positive effects on PON and ARE enzyme activities ofA.leptodactylus during its mating, pleopodal egg laying and pleopodal egg carrying periods.
Keywords: Biyoloji; Balıkçılık; Kimya; Uygulamalı; Zooloji